TECHNOLOGy AND NAQSHBANDI SUFISM: AN EMPIRICAL ANALYSIS OF ISMAIL AGA AND iSKENDER PAŞA BRANCHES - Himmet HÜLÜR (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
ATECHNOLOGy AND NAQSHBANDI SUFISM: AN EMPIRICAL ANALYSIS OF ISMAIL AGA AND iSKENDER PAŞA BRANCHES